The Development of the Putt.It.In Monitoring Device and the Establishment of Its Reliability: A Solution for Putting-In Analysis in Golf - Zahari, Taha; Mohd Azraai, Mohd Razman; Faeiz Azizi, Adnan; Anwar, P. P. A. Majeed; Rabiu Muazu, Musa (Kementerian Pendidikan Malaysia, 2017)
Background: The accurate transfer of information on the athletes’ performance in any sport is essential in enhancing the performance and overall coaching process. The provision of such information is favourable only if it is reliable. A cost-effective golf putting monitoring device namely the Putt.It.In was developed for analysing a golfers’ putting performance. Objectives: This study aims to investigate the reliability of the instrument in measuring the backswing distance, front swing distance, clubhead speed, ideal front swing distance and swing angle. Methods: A semiprofessional golfer (30 years of age ± 5.0 years’ experience) executed four strokes repeatedly from a distance of 2 m and 1 m using a Ram Zebra Mallet putter on a PGM golf mat. The intra-class correlation (ICC) coefficient is employed to test the reliability of the device whilst the Kolmogorov/Smirnov test was utilised to further reaffirm the reliability of the application in measuring the aforementioned parameters over test re-test between first two strokes of 2 m distance and the last two strokes of 1 m distance. Results: The ICC reveals 0.98 and 0.96 for both test 1 and 2, as well as a Cronbach’s Alpha of 0.99 and 0.96, respectively suggesting excellent consistencies in the overall observations. Moreover, the Kolmogorov/Smirnov test re-test indicates that there is no significant difference between the first two 2 m strokes p > 0.05, and subsequent two 1 m strokes p > 0.05 highlighting its ability to recognise the pattern of the strokes applied in the four successive strokes. Conclusion: The Putt.It.In monitoring device is found to be reliable in measuring the backswing distance, front swing distance, clubhead speed, ideal front swing distance and swing angle. Professional and semi-professional golfers as well coaches could consider Putt.It.In device in monitoring strokes related parameters to enhance their performance due to its effectiveness in providing information on putting performance.